2017
DOI: 10.5897/jvmah2016.0523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, gross pathological lesions and financial losses of bovine Fasciolosis in Arba Minch Municipal Abattoir, Gamo Gofa Zone, Southern Ethiopia

Abstract: A cross sectional study on bovine fasciolosis was carried out from October 2009 to April 2010 at Arba Minch Municipal abattoir with the aim of determining the prevalence and estimating financial loss. Out of the total 600 cattle examined during the study period, 203 were positive for Fasciola spp. infection with the prevalence rate of 33.83%. Fasciola gigantica was found to be the predominant Fasciola species affecting cattle slaughtered in the study area, 179 (88.18%) of the total livers positive for bovine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(8 reference statements)
1
1
1
Order By: Relevance
“…This indicates age has no effect on occurrence of fasciolosis. This report in line with the research works of Yosef, et al [15], Mandefrot, et al [28] and Ayele, et al (2018). This could be due to all age grouped animals were grazed on communal grazing field without discriminating at its age group at the same time and they feed on field together.…”
Section: Resultssupporting
confidence: 92%
“…This indicates age has no effect on occurrence of fasciolosis. This report in line with the research works of Yosef, et al [15], Mandefrot, et al [28] and Ayele, et al (2018). This could be due to all age grouped animals were grazed on communal grazing field without discriminating at its age group at the same time and they feed on field together.…”
Section: Resultssupporting
confidence: 92%
“…In contrast to this study higher prevalence of bovine fasciolosis have been reported by other researchers, such as [28] 57.58% in Jimma municipal abattoir, [29] 33% in Arba Minch, [11] 30% in Areka, [14] 32.3% in Adwa, [30] 28% in Kombolcha, [31] 90.7% in Gondar abattoir, [32] 39.95% in Bahir Dar, [33] 46.2% in Jimma abattoir, [15] 47.1% in Mettu abattoir and [34] 53.7% in Jimma Abattoir. The current findings are also lower prevalence than previous studies from other countries in African with the prevalence of 53.9% from Zambia, 63.8% from Tanzania, 38.5% from Uganda, 31.8% from Zimbabwe and 31.6% from Sudan reported by [35][36][37][38][39] respectively.…”
Section: No Of Animal Positivecontrasting
confidence: 99%
“…F. hepatica has a worldwide distribution but predominates in temperate zones while F. gigantica is found on most continents, primarily in tropical regions. Both F. hepatica and F. gigantica are transmitted by the snails of the family Lymnaesidae [66].…”
Section: General Description Of Fasciolosismentioning
confidence: 99%